VERBS OF PERCEPTION, THINKING, SPEAKING FROM THE POINT OF PSYCHOLOGY - Nazarova Manzura Nasrullaevna (Journal Park Publishing, 2024)
This article talks about verbs of perception of various types.
Keywords: perception, experience, speech, function, thinking, psychology.